Leadership and organization in the innovation economy - Johannessen, Jon-Arild (Emerald Publishing Limited, 2019)
Since the 1980s, society has undergone enormous change. From an industrialized society, focused on efficiency and productivity, there has been a transformation to a globalized knowledge society that focuses on creativity and innovation. And yet, management styles have stayed the same, not adapting to this crucial change. Here, leading innovation expert Jon-Arild Johannessen offers a replacement to traditional goal-driven management and New Public Management (NPM). These old styles of management promote efficiency and productivity, but hamper creativity and innovation. To counteract this, Johannessen suggests and outlines a new concept: strategic innovation management. Through a thorough analysis and debate of the demands of the new leadership role, and the demands of both employees and organizations, Johannessen explores the place of this new management style in the 21st century.For students and researchers of knowledge management, leadership, or innovation, this is an unmissable book exploring a fascinating new proposal.